Development of a facile and sensitive HPLC‐FLD method via fluorescence labeling for triterpenic acid bioavailability investigation. (17th January 2017) - You, Jinmao; Wu, Di; Zhao, Mei; Li, Guoliang; Gong, Peiwei; Wu, Yueyue; Guo, Yu; Chen, Guang; Zhao, Xianen; Sun, Zhiwei; Xia, Lian; Wu, Yongning
Abstract: Triterpenic acids are widely distributed in many fruits and are known for their medicinal benefits. The study of bioavailability has been an important task for a better understanding of the triterpenic acids. Although many methods based on fluorescence labeling for triterpenic acid determination have been established, these reported methods needed anhydrous conditions, which are not suitable for the convenient study of triterpenic acid bioavailability. Inspired by that, a versatile method, which overcomes the difficulty of the reported methods, has been first developed in this study. The novel method using 2‐[12‐benzo[ b ]acridin‐5‐ (12H)‐yl]‐acetohydrazide (BAAH) as the fluorescence labeling reagent coupled with high‐performance liquid chromatography with fluorescence detection was first developed for the study of triterpenic acid bioavailability. Furthermore, the labeling conditions have been optimized in order to achieve the best fluorescence labeling yield. Under the optimal conditions, the quantitative linear range of analytes was 2–1000 ng mL −1, and the correlation coefficients were >0.9998. The detection limits for all triterpenic acid derivatives were achieved within the range of 0.28–0.29 ng mL −1 . The proposed method was successfully applied to the study of triterpenic acid bioavailability with excellent applicability and good reproducibility.